2023
DOI: 10.3389/fcell.2023.1094356
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial calcium cycling in neuronal function and neurodegeneration

Abstract: Mitochondria are essential for proper cellular function through their critical roles in ATP synthesis, reactive oxygen species production, calcium (Ca2+) buffering, and apoptotic signaling. In neurons, Ca2+ buffering is particularly important as it helps to shape Ca2+ signals and to regulate numerous Ca2+-dependent functions including neuronal excitability, synaptic transmission, gene expression, and neuronal toxicity. Over the past decade, identification of the mitochondrial Ca2+ uniporter (MCU) and other mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 339 publications
0
13
0
Order By: Relevance
“…Here, the mitochondrial Ca 2+ levels in the analyzed cell lineages do only partially follow the observed MMP or cytosolic Ca 2+ levels. However, these parameters are also affected by secondary mechanisms such as plasmalemmal and ER Ca 2+ transporters or the activity of the uncoupling proteins and the ATP-synthase of the inner mitochondrial membrane (IMM) 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the mitochondrial Ca 2+ levels in the analyzed cell lineages do only partially follow the observed MMP or cytosolic Ca 2+ levels. However, these parameters are also affected by secondary mechanisms such as plasmalemmal and ER Ca 2+ transporters or the activity of the uncoupling proteins and the ATP-synthase of the inner mitochondrial membrane (IMM) 46 .…”
Section: Discussionmentioning
confidence: 99%
“…but also generates oxygen stress and leads to damage of DNA, lipids, and proteins. Moreover, various signaling pathways including Ca 2+ and steroid hormone precursors are affected 46,[48][49][50] . Among the numerous hypotheses on the etiology of psychiatric and neurological disorders, the role of mitochondria in the pathology of mental illness is attracting increasing interest.…”
Section: Mitochondrial Dysfunction Does Not Only Affect Bioenergetics...mentioning
confidence: 99%
“…Normally, the free intracellular concentration of Ca 2+ is very low, but when the cells are in an activated stage, its intracellular concentration is increased. 129 Upregulation of intracellular Ca 2+ levels and high pH intracellular levels are associated with several NDs and age-related disorders 76,80,130 ; based on these findings, we present a scheme in which Duitama et al 76 indicated how the alterations in Ca 2+ homeostasis induce the modifications of various cellular processes 80 (Fig. 16).…”
Section: Gate Mechanisms and Biological Functions Of Trp Channelsmentioning
confidence: 92%
“…Normally, the free intracellular concentration of Ca 2+ is very low, but when the cells are in an activated stage, its intracellular concentration is increased. 129…”
Section: Transient Receptor Potential Channels: Biological Features A...mentioning
confidence: 99%
“…Mitochondrial Ca 2+ flux was monitored using the low-affinity fluorescent label Calcium Green 5N, as a Ca 2+ indicator (Kd~14 µM) (A) Schematics of mitochondrion with MCU and NCLX channels. MCU passes Ca 2+ inside the mitochondrion (Ca 2+ influx); NCLX passes Na + or Li + inside the mitochondrion in exchange for Ca 2+ transport outside (Ca 2+ efflux) (Rossi, Pizzo, and Filadi, 2019;Walters and Usachev, 2023). (B) Ca 2+ -induced fluorescence as a measure of Ca 2+ influx through MCU and Ca 2+ efflux through NCLX in exchange for Na + .…”
Section: Ca 2+ Fluorescence Experimentsmentioning
confidence: 99%